Interactions among cyclists riding the wrong way on the bicycle path - Claudia Leschik; Imanol Irizar da Silva; Kay Gimm; Marek Junghans (Traffic Safety Research)
Cycling in the opposite direction can lead to many critical interaction situations and sometimes to severe crashes among cyclists. Unfortunately, no official statistics are kept of such situations in Germany. Since the number of cyclists increases in many locations in Germany faster than the cycling infrastructure improves, we can expect more of such dangerous situations in the near future. To reduce their number and severity and to develop realistic simulation models, it is essentially important to understand, how cyclists interact with each other in this particular scenario of wrong-way cycling and what consequences result for safety and cycling behaviour. This paper presents methodology and descriptive results of a traffic observation study at a signalled urban intersection in Braunschweig, Germany, with separated bicycle and footpaths. At this instrumented intersection, road user trajectories were recorded and analysed with regard to identify interactions between normal and wrong-way cyclists, and to find behavioural patterns. It appeared that several different behavioural patterns, for instance switching from bicycle path to footpath, occurred, speeds of wrong-way cyclists were slower. The distances before switching appeared to be different in some of the patterns while in others they appeared to be similar.